PENGARUH SUPERVISI KLINIS TERHADAP PENATALAKSANAAN UNIVERSAL PRECAUTION OLEH PERAWAT (LITERATURE REVIEW) - Wati, Ira Mehara (LPPM BSI Bandung, 2014)
Abstract - The cases of nosocomial infection and low safety nurses Is still rampant and it make health care provided has not been said to be good. Culture of safety for patients or nurses are influenced by universal precaution containment procedures that can not be separated with clinical supervision. Implementation of clinical supervision is to help evaluate nursing actions so in accordance with the standard. During the implementation of clinical supervision in the management of universal precautions has not been done in a structured and not optimally. This article aims to identify and review of previous studies related to the influence of universal precautions supervise management. The method used is to review the literature of nursing, medicine, and public health from tahun1987 to 2013 using 12 related articles of universal precautions and supervision as reference. The results of the literature review showed that clinical supervision affect the application of universal precautions by nurses. The conclusion obtained is that clinical supervision is very instrumental in the achievement of the implementation of nursing practice to conform to the standards that have been defined, in this case in order to achieve universal culture of safety precautions so as to prevent infection and accidents for nurses.Keyword : Universal Precautions, Supervision, Safety Culture, Infection, Nosocomial Bibliography: 29, 1998-2013 Abstrak - Masih maraknya kasus infeksi nosocomial dan rendahnya keselamatan kerja perawat membuat pelayanan kesehatan yang diberikan belum dikatakan baik. Budaya safety bagi pasien atau perawat dipengaruhi oleh penatalaksaan universal precaution yang tidak terlepas dengan pengawasan atau supervisi klinis. Pelaksanaan supervisi klinis dimaksud untuk membantu mengevaluasi tindakan keperawatan sehingga sesuai dengan standar. Selama ini pelaksanaan supervisi klinis dalam penatalaksanaan universal precaution belum dilakukan secara terstruktur dan optimal. Artikel ini bertujuan untuk mengidentifikasi dan mengulas penelitian sebelumnya terkait pengaruh supervisi terhadap penatalaksanaan universal precaution.Metode yang digunakan adalah mengulas literatur keperawatan, kedokteran, dan kesehatan masyarakat dari tahun1987 sampai 2013 dengan menggunakan 12 artikel terkait universal precaution dan supervisi sebagai referensiHasil ulasan literatur menunjukan bahwa supervisi klinis berpengaruh terhadap penerapan universal precaution oleh perawat.Kesimpulan yang didapatkan adalah bahwa supervisi klinis amat berperan dalam tercapainya penerapan praktik keperawatan agar sesuai dengan standar yang sudah ditetapkan, dalam hal ini adalah universal precaution guna tercapainya budaya safety sehingga mencegah infeksi dan kecelakaan kerja bagi perawat. Kata Kunci : Universal Precaution, Supervisi, Budaya Safety, Infeksi, NosocomialBibliografi : 29, 1998-2013